1975
DOI: 10.1207/s15328023top0203_3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Mastery Approaches to Teaching Introductory Psychology

Abstract: Treatment effects are more convincing for weekly quizzes than for examinations, but Programmed Student Achievement looks best in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 6 publications
(4 reference statements)
1
0
0
Order By: Relevance
“…While LFM and PSI allowed unlimited opportunities for reassessment, our method was designed with the practical constraints faced by higher education instructors today in mind. Additionally, Nation and Roop (1975) observed that capping reattempts could motivate students to devote more time and energy into the learning of course material, further supporting our decision to limit reattempt opportunities. To test the impact of our newly devised approach to mastery on undergraduate learning, we assessed the following: student knowledge growth (did students perform better on the final exam than they did on the pretest?…”
Section: A New Approach To Mastery Learningsupporting
confidence: 57%
“…While LFM and PSI allowed unlimited opportunities for reassessment, our method was designed with the practical constraints faced by higher education instructors today in mind. Additionally, Nation and Roop (1975) observed that capping reattempts could motivate students to devote more time and energy into the learning of course material, further supporting our decision to limit reattempt opportunities. To test the impact of our newly devised approach to mastery on undergraduate learning, we assessed the following: student knowledge growth (did students perform better on the final exam than they did on the pretest?…”
Section: A New Approach To Mastery Learningsupporting
confidence: 57%